Evaluation of a Multi-Season, Community-Based Larval Source Management Program on Bioko Island, Equatorial Guinea - García, Guillermo A.; Fuseini, Godwin; Mba Nlang, Jose Antonio; Nsue Maye, Valeriano Olo; Bela, Nestor Rivas; Wofford, Rachel N.; Weppelmann, Thomas A.; Matulis, Graham; Efiri, Prudencio Bibang; Smith, Jordan M.; Rivas, Matilde Riloha; Phiri, Wonder Philip; et al. (Frontiers in Tropical Diseases, 2022)
Background In 2015 and 2016, the Bioko Island Malaria Control Project (BIMCP) introduced a pilot larvicide program, which recruited local volunteers to assess the sustainability and effectiveness of community-led larval source management. This study evaluates the effectiveness of the community-led LSM program to determine if this type of intervention could be used as a sustainable malaria control method on Bioko Island. Methods The pilot program was split into two phases, both taking place between February and December, with phase I in 2015 and phase II in 2016. During phase I, the BIMCP team assisted in identifying and treating Anopheles species mosquito breeding habitats. During phase II, community volunteers, with supervision from designated community leaders, identified and treated breeding habitats. Larval source management took place at thirteen locations around the Island during both phases. Human landing catches were conducted at seven sentinel sites once every month for the duration of the study period to determine average nightly biting rates. Results During phase I, 1,033 breeding sites were identified with a 100% treatment coverage rate. Only 970 breeding sites were identified in phase II with a 75% treatment coverage rate, a significant decrease from phase I (p<0.001). Between phase I and phase II, larvicide usage also decreased by 45% (95% CI: 32, 59%, p=0.003). However, excluding the sentinel site Balboa, vector density showed a nonsignificant (p=0.272) relationship between phase I and phase II. Conclusion Overall, community-based larval source management can be effective with strong operational management and oversight. However, repeated training and evaluation will be necessary to monitor the effectiveness and sustainability of such interventions.